Efeito de diferentes soluções irrigadoras sobre a resistência adesiva de pinos de fibra de vidro com utilização de cimento autoadesivo - Seballos, Vívian Gehm (2016)
The purpose of this study is to evaluate the effect of different irrigatins on bond strength of fiber posts cemented with RelyX U200. Eighty single-rooted premolars were sectioned at 14 mm from the apex, prepared with ProTaper Universal system until F3 instrument, and filled with F3 master cone and AH Plus sealer. Root canal filling was partially removed, remaining 4 mm of guta-percha at the apical third. Specimens were randomly divided into 8 groups (n=10), according to the irrigant used during root canal preparation and before fiber post cementation (dentin surface treatment), as described: SS: 0,9% saline solution (control group); CHX: 2% chlorhexidine; 1%NaOCl: 1% sodium hypochlorite; 2,5%NaOCl: 2,5% sodium hypochlorite; 5%NaOCl: 5% sodium hypochlorite; 1%CaOCl: 1% calcium hypochlorite; 2,5%CaOCl: 2,5% calcium hypochlorite; e 5%CaOCl: 5% calcium hypochlorite. For each group, irrigation was performed continuously with 2ml. Exacto N2 glass fiber posts were cemented with RelyX U200. The specimens were sectioned providing 3 slices, one for each root third and the push-out test was performed. Optical microscopy was used to analyze the failure mode. Bond strength means were calculated and ANOVA and Bonferroni tests were used for statistical analysis. SS showed higher mean of bond strength values (11.47MPa), than all NaOCl and CaOCl groups, which showed similar values to CHX (7.56Mpa ± 2:47). Adhesive failures at cement/dentin interface were predominant (58.33%). NaOCl and CaOCl negatively affect the bond strength of fiber posts to root dentine when cemented with sef-adhesive resin cement; however the concentration of NaOCl and CaOCl did not affect this outcome.